Analisis Program Field Study dalam Meningkatkan Kemampuan Mengajar Mahasiswa Program Magister PAI UIN Sunan Kalijaga Yogyakarta - Ulfah, Suci Nurmaya; Arifi, Ahmad; Fatkhan, Muhammad; Fitria, Anis Fajar (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2024)
Effective educators are essential to foster a quality generation, so their competencies must continue to be developed. There are special education programs for those who want to become educators at the higher education level. Where students who show extraordinary academic achievement are identified as prospective future educators, this study intends to examine the impact of the Field Study Program for students of the Islamic Religious Education (PAI) Master program on learning capacity to achieve mastery of the course. This study uses a qualitative methodology, namely descriptive research design. This study's participants were postgraduate students taking the PAI Master program at UIN Sunan Kalijaga Yogyakarta. The results of this study indicate that field study has a significant way to improve student's learning abilities. The method includes observation, implementation, and assessment of the learning process to provide adequate assistance. This practice allows them to demonstrate their teaching talents as prospective educators.